2011
DOI: 10.1134/s1062739147050194
|View full text |Cite
|
Sign up to set email alerts
|

Study of diethyl dithiophosphate adsorption on chalcopyrite and tennantite at varied pHs

Abstract: The kinetics of diethyl dithiophosphate adsorption on chalcopyrite and tennantite has been studied by UV-visible spectroscopy at pH values of 4, 6, and 9. The concentration of diethyl dithiophosphate in the solution has been monitored as a function of time and pH for both minerals. It was found that the adsorption tendency of diethyl dithiophosphate on both minerals decreased with the increasing pH treatments. This is due to the existence of metal hydroxide species onto the mineral surface in more alkaline con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In Figure 11, the isotherm of chalcopyrite attains the plateau value at 3.6 µmol•m −2 , thus indicating a 0.8 monolayer. Previously, Petrus et al [28] observed less than a monolayer coverage of dithiophosphate on chalcopyrite at an equilibrium concentration 1.54 × 10 −5 M. Our findings are in accordance with these studies, indicating less than a monolayer adsorption on the chalcopyrite surface followed by a sudden increase in adsorption density above concentration 1.87 × 10 −4 M. The increase after a plateau region can be attributed to precipitate formation in the bulk of solution, or another assertion can be multilayers of surface product are adsorbed on the chemisorbed monolayer [7,17,25]. The chalcocite-xanthate adsorption isotherm indicates a marginal increase in adsorption density, followed by a steep rise in the slope which corresponds to the onset of adsorption due to the accumulation of the collector at equilibrium concentration 9.2 × 10 −6 M. These results show a less than monolayer coverage of DBD on bornite where the adsorption density is merely 3.2 µmol•m −2 .…”
Section: Adsorption Studiesmentioning
confidence: 96%
“…In Figure 11, the isotherm of chalcopyrite attains the plateau value at 3.6 µmol•m −2 , thus indicating a 0.8 monolayer. Previously, Petrus et al [28] observed less than a monolayer coverage of dithiophosphate on chalcopyrite at an equilibrium concentration 1.54 × 10 −5 M. Our findings are in accordance with these studies, indicating less than a monolayer adsorption on the chalcopyrite surface followed by a sudden increase in adsorption density above concentration 1.87 × 10 −4 M. The increase after a plateau region can be attributed to precipitate formation in the bulk of solution, or another assertion can be multilayers of surface product are adsorbed on the chemisorbed monolayer [7,17,25]. The chalcocite-xanthate adsorption isotherm indicates a marginal increase in adsorption density, followed by a steep rise in the slope which corresponds to the onset of adsorption due to the accumulation of the collector at equilibrium concentration 9.2 × 10 −6 M. These results show a less than monolayer coverage of DBD on bornite where the adsorption density is merely 3.2 µmol•m −2 .…”
Section: Adsorption Studiesmentioning
confidence: 96%
“…Limited information is available about the interaction of DTPIs with arsenic-bearing sulphides, of which enargite and tennantite (Cu12As4S13) are the most significant in copper ore bodies (Petrus et al, 2011a). Of these two minerals, the adsorption of the related dithiophosphate (DTP) collector onto tennantite has been investigated (Petrus et al, 2011a;Petrus et al, 2011b), and the flotation response of enargite with several collectors, including isopropyl xanthate and diisobutyl dithiophosphate, at pH 10.5, has been studied using a modified Halimond tube .…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…Investigation of whether collector adsorption at positive potentials is electrochemically reversible by subsequent application of cathodic potentials, as well as detailed investigation of the mechanisms of collector adsorption, as has been done for other minerals, (Güler et al 2005, Petrus et al 2011, Buckley et al 2003, is also necessary.…”
Section: Future Directions and Recommendationsmentioning
confidence: 99%